Trade openness and the nutrient use of nations. (4th December 2018) - Dang, Qian; Konar, Megan; Debaere, Peter
Abstract: To contribute to the debate over globalization and the environment we ask the question: what is the impact of trade openness on the nutrient use of nations? We address this question by using econometric methods to quantify the causal relationship between the trade openness and the nutrient use of nations on a global scale. In our empirical analysis we go beyond a cross-sectional analysis. We exploit time-series variation for an unbalanced panel of countries that spans the time period 2001–2014 (1027 total observations). By using a panel data analysis we are able to use fixed effects and better control for unobservable heterogeneity. We also explicitly consider how the openness of a country to trade may interact with its comparative advantage which determines its relative specialization in production, and hence its export strength as well as its import needs. We find that trade openness on average does not significantly impact nutrient use. However, there is evidence that as countries become more open and more capital abundant their nutrient use is reduced. This finding is in line with previous research that shows that trade openness does not have a negative impact on the environment. Our findings have both scientific and policy relevance as we strive to untangle causal relationships in the global food supply chain and determine its environmental impacts.